The Socio-Economic Dimension of the Late Medieval Lordship. Introductory Remarks to the Lombard Case (Studi di storia medioevale e di diplomatica - Nuova Serie, 2020)
The essays collected here investigate, from various perspectives, the economic impact of rural lordship in Late Medieval Lombardy. In the introduction, the editors offer an overview of the results achieved by the research.
Keywords: Rural lordship; Lombardy; Late Middle Ages; pervasiveness; power; forms of management